Omega-3 Polyunsaturated Fatty Acids Inhibited Tumor Growth via Preventing the Decrease of Genomic DNA Methylation in Colorectal Cancer Rats. (2nd January 2016) - Huang, Qionglin; Wen, Juan; Chen, Guangzhao; Ge, Miaomiao; Gao, Yihua; Ye, Xiaoxia; Liu, Chunan; Cai, Chun
ABSTRACT: Omge-3 polyunsaturated fatty acids (PUFAs) exhibited significant effect in inhibiting various tumors. However, the mechanisms of its anticancer role have not been fully demonstrated. The declination of 5-methylcytosine (5 mC) was closely associated with poor prognosis of tumors. To explore whether omega-3 PUFAs influences on DNA methylation level in tumors, colorectal cancer (CRC) rat model were constructed using N-methyl phosphite nitrourea and omega-3 PUFAs were fed to part of the rats during tumor induction. The PUFAs contents in the rats of 3 experimental groups were measured using gas chromatography and 5 mC level were detected by liquid chromatography tandem mass spectrometry. The results showed that tumor incidence in omega-3 treated rats was much lower than in CRC model rats, which confirmed significant antitumor role of omega-3 PUFAs. Six PUFA members categorized to omega-3 and omega-6 families were quantified and the ratio of omega-6/omega-3 PUFAs was remarkably lower in omega-3 PUFAs treatment group than in CRC model group. 5 mC content in omega-3 PUFAs treated rats was higher than in CRC model rats, suggesting omega-3 PUFAs promoted 5 mC synthesis. Therefore, omega-3 PUFAs probably inhibited tumor growth via regulating DNA methylation process, which provided a novel anticancer mechanism of omega-3 PUFAs from epigenetic view.